Altered glycosylation of complexed native IgG molecules is associated with disease activity of systemic lupus erythematosus - Sjowall, Christopher; Zapf, J.; Von Loehneysen, S.; Magorivska, I.; Biermann, M.; Janko, Christina; Winkler, Sophie; Bilyy, R.; Schett, Georg; Herrmann, Martin; Munoz Becerra, Luis (Lupus, 2015)
In addition to the redundancy of the receptors for the Fc portion of immunoglobulins, glycans result in potential ligands for a plethora of lectin receptors found in immune effector cells. Here we analysed the exposure of glycans containing fucosyl residues and the fucosylated tri-mannose N-type core by complexed native IgG in longitudinal serum samples of well-characterized patients with systemic lupus erythematosus. Consecutive serum samples of a cohort of 15 patients with systemic lupus erythematosus during periods of increased disease activity and remission were analysed. All patients fulfilled the 1982 American College of Rheumatology classification criteria. Sera of 15 sex- and age-matched normal healthy blood donors served as controls. The levels and type of glycosylation of complexed random IgG was measured with lectin enzyme-immunosorbent assays. After specifically gathering IgG complexes from sera, biotinylated lectins Aleuria aurantia lectin and Lens culinaris agglutinin were employed to detect IgG-associated fucosyl residues and the fucosylated tri-mannose N-glycan core, respectively. In sandwich-ELISAs, IgG-associated IgM, IgA, C1q, C3c and C-reactive protein (CRP) were detected as candidates for IgG immune complex constituents. We studied associations of the glycan of complexed IgG and disease activity according to the physician's global assessment of disease activity and the systemic lupus erythematosus disease activity index 2000 documented at the moment of blood taking. Our results showed significantly higher levels of Aleuria aurantia lectin and Lens culinaris agglutinin binding sites exposed on IgG complexes of patients with systemic lupus erythematosus than on those of normal healthy blood donors. Disease activity in systemic lupus erythematosus correlated with higher exposure of Aleuria aurantia lectin-reactive fucosyl residues by immobilized IgG complexes. Top levels of Aleuria aurantia lectin-reactivity were found in samples taken during the highest activity of systemic lupus erythematosus. Our results show that native circulating IgG complexes from active systemic lupus erythematosus patients expose fucosyl residues and their glycan core is accessible to soluble lectins. Two putative mechanisms may contribute to the increased exposure of these glycans: (1) the canonical N-glycosylation site of the IgG-CH2 domain; (2) an IgG binding non-IgG molecule, like complement or C-reactive protein. In both cases the complexed IgG may be alternatively targeted to lectin receptors of effector cells, e.g. dendritic cells.
EVALuna2:13017

Autoantibodies against galectins are associated with antiphospholipid syndrome in patients with systemic lupus erythematosus - Sarter, Kerstin; Janko, Christina; Andre, Sabine; Munoz, Luis Enrique; Schorn, Christine; Winkler, Sophie; Rech, Jürgen; Kaltner, Herbert; Lorenz, Hanns-Martin; Schiller, Martin; Andreoli, Laura; Manfredi, Angelo A.; et al. (Glycobiology, 2013)
The presence of autoantibodies against immunoregulatory effectors can be relevant for onset and/or the progression of autoimmune disease. Emerging insights into an immunological activity profile including a role as opsonins give reason to systematically monitor sera of patients for immunoglobulin G (IgG) autoantibodies, preferably for several galectins at the same time. Here, we report on a study of chronic inflammatory rheumatic diseases, i.e. systemic lupus erythematosus (SLE; pilot cohort p, n = 40; confirmation cohort c, n = 109), rheumatoid arthritis (RA; p, n = 32; c, n = 25) and primary antiphospholipid syndrome (APS; c, n = 64). Enzyme-linked immunosorbent assay-based series using galectin-1, -2, -3, -4, -7, -8 and -9 and natural processing products, i.e. the truncated version of galectin-3 and the N-terminal domains of galectin-4, -8 and -9, were performed. Normal healthy donors (p, n = 20; c, n = 21) and patients with paraproteins (c, n = 19) served as controls. Highly significant optical density-value readings for IgG autoantibodies were consistently detected for the proto-type galectin-7 (SLE) and the tandem repeat-type galectin-8 and -9 (SLE and RA). Their presence was independent from the autoantibody status against double-stranded DNA (for patients with SLE) or a rheumatoid factor (for patients with RA), respectively. Importantly, anti-galectin-2 autoantibodies highly significantly correlated with the appearance of a secondary APS in patients with SLE so that this parameter may serve as an additional biomarker for APS. Equally of note, the presence of IgG autoantibodies against galectins capable to act as an opsonin may contribute to a sustained immune dysregulation in patients with chronic inflammatory rheumatic diseases. © The Author 2012. Published by Oxford University Press. All rights reserved.
CRIS-Team Scopus Importer:2021-02-03
Keywords: antiphospholipid syndrome; autoantibodies; galectins; systemic lupus erythematosus

Bone tissue engineering using adipose-derived stem cells and endothelial cells: Effects of the cell ratio - Mutschall, Hilkea; Winkler, Sophie; Weisbach, Volker Günter; Arkudas, Andreas; Horch, Raymund E.; Steiner, Dominik (Journal of Cellular and Molecular Medicine, 2020)
The microvascular endothelial network is essential for bone formation and regeneration. In this context, endothelial cells not only support vascularization but also influence bone physiology via cell contact-dependent mechanisms. In order to improve vascularization and osteogenesis in tissue engineering applications, several strategies have been developed. One promising approach is the coapplication of endothelial and adipose derived stem cells (ADSCs). In this study, we aimed at investigating the best ratio of human umbilical vein endothelial cells (HUVECs) and osteogenic differentiated ADSCs with regard to proliferation, apoptosis, osteogenesis and angiogenesis. For this purpose, cocultures of ADSCs and HUVECs with ratios of 25%:75%, 50%:50% and 75%:25% were performed. We were able to prove that cocultivation supports proliferation whereas apoptosis was unidirectional decreased in cocultured HUVECs mediated by a p-BAD-dependent mechanism. Moreover, coculturing ADSCs and HUVECs stimulated matrix mineralization and the activity of alkaline phosphatase (ALP). Increased gene expression of the proangiogenic markers eNOS, Flt, Ang2 and MMP3 as well as sprouting phenomena in matrigel assays proved the angiogenic potential of the coculture. In summary, coculturing ADSCs and HUVECs stimulates proliferation, cell survival, osteogenesis and angiogenesis particularly in the 50%:50% coculture.
CRIS-Team Scopus Importer:2020-05-22
Keywords: ADSC; angiogenesis; bone tissue engineering; HUVEC; osteogenesis

Enhanced vascularization and de novo tissue formation in hydrogels made of engineered RGD-tagged spider silk proteins in the arteriovenous loop model - Steiner, Dominik; Winkler, Sophie; Heltmann-Meyer, Stefanie; Trossmann, Vanessa T.; Fey, Tobias; Scheibel, Thomas; Horch, Raymund E.; Arkudas, Andreas (Biofabrication, 2021)
Due to its low immunogenic potential and the possibility to fine-tune their properties, materials made of recombinant engineered spider silks are promising candidates for tissue engineering applications. However, vascularization of silk-based scaffolds is one critical step for the generation of bioartificial tissues and consequently for clinical application. To circumvent insufficient vascularization, the surgically induced angiogenesis by means of arteriovenous loops (AVL) represents a highly effective methodology. Here, previously established hydrogels consisting of nano-fibrillary recombinant eADF4(C16) were transferred into Teflon isolation chambers and vascularized in the rat AVL model over 4 weeks. To improve vascularization, also RGD-tagged eADF4(C16) hydrogels were implanted in the AVL model over 2 and 4 weeks. Thereafter, the specimen were explanted and analyzed using histology and microcomputed tomography. We were able to confirm biocompatibility and tissue formation over time. Functionalizing eADF4(C16) with RGD-motifs improved hydrogel stability and enhanced vascularization even outperforming other hydrogels, such as fibrin. This study demonstrates that the scaffold ultrastructure as well as biofunctionalization with RGD-motifs are powerful tools to optimize silk-based biomaterials for tissue engineering applications.
CRIS-Team WoS Importer:2021-08-06

Human Umbilical Vein Endothelial Cell Support Bone Formation of Adipose-Derived Stem Cell-Loaded and 3D-Printed Osteogenic Matrices in the Arteriovenous Loop Model - Winkler, Sophie; Mutschall, Hilkea; Biggemann, Jonas; Fey, Tobias; Greil, Peter; Körner, Carolin; Weisbach, Volker Günter; Meyer-Lindenberg, Andrea; Arkudas, Andreas; Horch, Raymund E.; Steiner, Dominik (Tissue Engineering - Part A, 2020)
Introduction:For the regeneration of large volume tissue defects, the interaction between angiogenesis and osteogenesis is a crucial prerequisite. The surgically induced angiogenesis by means of an arteriovenous loop (AVL), is a powerful methodology to enhance vascularization of osteogenic matrices. Moreover, the AVL increases oxygen and nutrition supply, thereby supporting cell survival as well as tissue formation. Adipose-derived stem cells (ADSCs) are interesting cell sources because of their simple isolation, expansion, and their osteogenic potential. This study targets to investigate the coimplantation of human ADSCs after osteogenic differentiation and human umbilical vein endothelial cells (HUVECs), embedded in a vascularized osteogenic matrix of hydroxyapatite (HAp) ceramic for bone tissue engineering. Materials and Methods:An osteogenic matrix consisting of HAp granules and fibrin has been vascularized by means of an AVL. Trials in experimental groups of four settings were performed. Control experiments without any cells (A) and three cell-loaded groups using HUVECs (B), ADSCs (C), as well as the combination of ADSCs and HUVECs (D) were performed. The scaffolds were implanted in a porous titanium chamber, fixed subcutaneously in the hind leg of immunodeficient Rowett Nude rats and explanted after 6 weeks. Results:In all groups, the osteogenic matrix was strongly vascularized. Moreover, remodeling processes and bone formation in the cell-containing groups with more bone in the coimplantation group were proved successful. Conclusion:Vascularization and bone formation of osteogenic matrices consisting of ADSCs and HUVECs in the rat AVL model could be demonstrated successfully for the first time. Hence, the coimplantation of differentiated ADSCs with HUVECs may therefore be considered as a promising approach for bone tissue engineering. Impact statement Due to their low donor-site morbidity, osteogenic potential and their good cell expansion, human adipose-derived stem cell is an interesting cell source. The goal of this study is to transfer thein vitroresults of increasing osteogenic potential upon cocultivation with human umbilical vein endothelial cell, to the rat arteriovenous loop model within the next step. Without using growth factors, the biomaterials, fibrin and HAp, which have already been successfully applied in clinical practice, are supposed to support bone formation by the implanted cells. The results demonstrated that vascularized bone tissue was formed in the cell-containing groups after 6 weeks.
CRIS-Team WoS Importer:2020-10-23

Intrinsic Vascularization of Recombinant eADF4(C16) Spider Silk Matrices in the Arteriovenous Loop Model - Steiner, Dominik; Lang, Gregor; Fischer, Laura; Winkler, Sophie; Fey, Tobias; Greil, Peter; Scheibel, Thomas; Horch, Raymund E.; Arkudas, Andreas (Tissue Engineering: Parts A, B, and C, 2019)
The surgically induced angiogenesis by means of arteriovenous (AV) loops represents a powerful method to significantly enhance vascularization of biomaterials. Regarding tissue engineering applications, spider silk is a promising biomaterial with a good biocompatibility and slow biodegradation. This study aims at investigating vascularization as well as de novo tissue formation of fibrous matrices made of electro-spun (ES) or wet-spun (WS) engineered ADF4(C16) spider silks in the rat AV loop model. Either ES or WS spider silk fibrous matrices were filled into Teflon chambers. Intrinsic vascularization was induced by means of an AV loop. After 4 weeks of vascularization, de novo tissue formation and biocompatibility were analyzed. Regardless of their significantly differing fiber diameters, both ES and WS eADF4(C16) fiber matrices displayed a good biocompatibility and initiated de novo tissue formation as well as vessel formation. Both matrices demonstrated partial vascularization originating from the AV loop, with more vessels in spider silk matrices with lower fiber diameters. We were able to demonstrate intrinsic vascularization of spider silk fibrous matrices by means of the AV loop. Moreover, our study indicates that the adjustment of the fiber diameter of engineered spider silks enables new possibilities to optimize vascularization.
CRIS-Team WoS Importer:2019-05-17

The Adipose-Derived Stem Cell and Endothelial Cell Coculture System-Role of Growth Factors? - Steiner, Dominik; Mutschall, Hilkea; Winkler, Sophie; Horch, Raymund E.; Arkudas, Andreas (Cells, 2021)
Adequate vascularization is a fundamental prerequisite for bone regeneration, formation and tissue engineering applications. Endothelialization of scaffold materials is a promising strategy to support neovascularization and bone tissue formation. Besides oxygen and nutrition supply, the endothelial network plays an important role concerning osteogenic differentiation of osteoprogenitor cells and consecutive bone formation. In this study we aimed to enhance the growth stimulating, proangiogenic and osteogenic features of the ADSC and HUVEC coculture system by means of VEGFA165 and BMP2 application. We were able to show that sprouting phenomena and osteogenic differentiation were enhanced in the ADSC/HUVEC coculture. Furthermore, apoptosis was unidirectionally decreased in HUVECs, but these effects were not further enhanced upon VEGFA165 or BMP2 application. In summary, the ADSC/HUVEC coculture system per se is a powerful tool for bone tissue engineering applications.
CRIS-Team WoS Importer:2021-09-10